Purification and Properties of Primary and Secondary Alcohol Dehydrogenases from Thermoanaerobacter ethanolicus - Bryant, Frank O. (1988)
Thermoanaerobacter ethanolicus (ATCC 31550) has primary and secondary alcohol dehydrogenases. The two enzymes were purified to homogeneity as judged from sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel filtration. The apparent M(r)s of the primary and secondary alcohol dehydrogenases are 184,000 and 172,000, respectively. Both enzymes have high thermostability. They are tetrameric with apparently identical subunits and contain from 3.2 to 5.5 atoms of Zn per subunit. The two dehydrogenases are NADP dependent and reversibly convert ethanol and 1-propanol to the respective aldehydes. The V(m) values with ethanol as a substrate are 45.6 μmol/min per mg for the primary alcohol dehydrogenase and 13 μmol/min per mg for the secondary alcohol dehydrogenase at pH 8.9 and 60°C. The primary enzyme oxidizes primary alcohols, including up to heptanol, at rates similar to that of ethanol. It is inactive with secondary alcohols. The secondary enzyme is inactive with 1-pentanol or longer chain alcohols. Its best substrate is 2-propanol, which is oxidized 15 times faster than ethanol. The secondary alcohol dehydrogenase is formed early during the growth cycle. It is stimulated by pyruvate and has a low K(m) for acetaldehyde (44.8 mM) in comparison to that of the primary alcohol dehydrogenase (210 mM). The latter enzyme is formed late in the growth cycle. It is postulated that the secondary alcohol dehydrogenase is largely responsible for the formation of ethanol in fermentations of carbohydrates by T. ethanolicus.